Knowledge and Attitude Towards Short Birth Interval among Rural Women who Gave Birth in the Last Three Years at Dembecha District, Northwest Ethiopia, 2019 - Mastewal Belayneh Aklil; Wubedle Zelalem Temesgan; Kiber Temesgen Anteneh; Tibeb Zena Debele (SAGE Publishing, 2022)
Background A woman can have fewer children when intervals between consecutive births are optimal. This has great importance for the well-being of women, pregnancy outcomes, and the long-term health of children under the age of five. We can save 2millon of the 11 million deaths of children under the age of five per year by avoiding short birth intervals. It is affected by the knowledge and attitude of women, particularly rural women, who had a high fertility rate. To our deep review, this is the first study done in Ethiopia. Hence, this study aimed to assess knowledge and attitude towards short birth intervals and associated factors among rural women who gave birth in the last three years at Dembecha district, northwest Ethiopia. Method A community-based cross-sectional study was conducted from September 20 to October 20, 2019. A cluster sampling technique was employed to select the study participants and data were collected using a pre-tested, semi-structured, interviewer-administered questionnaire. Bivariable and multivariable logistic regression model was fitted to identify factors associated with knowledge and attitude towards short birth interval. The level of significant association was declared using the adjusted odds ratio (AOR) with 95% confidence interval (CI) and a p-value of <0.05. Result From the total study participants, 66.4% (95% CI: 63.0-70.0) had good knowledge and 45.9% (95% CI: 42.3-49.8) had a positive attitude towards short birth intervals. In multivariable logistic regression: marital status, antenatal care follow-up, maternal occupation, and wealth status were significantly associated with knowledge. In addition, antenatal care follow-up and maternal occupation were significantly associated with attitude. Conclusion Majority of the participants had poor knowledge and a positive attitude towards short birth intervals. Hence, interventions should be done to optimize women's knowledge and attitude towards short birth intervals by enhancing antenatal care utilization.